Association analysis of a GSTP1 functional polymorphism with methamphetamine dependence and associated symptoms in a multiethnic Malaysian population - Hasif Adli Zakariah,; Nik Nur Syaheerah Nik Abdul Rahman,; Wu, Yuan Seng; Suzaily Wahab,; Rusdi Abdul Rashid,; Sim, Maw Shin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Methamphetamine (METH) is a psychostimulant that is highly addictive and has been widely linked to the adverse effect on brain. METH-induced oxidative stress can be effectively protected by glutathione S-transferases (GSTs). Genetic polymorphism of GST gene family may affect the susceptibility of METH users to its dependence and associated symptoms. Therefore, this study investigated the association of a functional single nucleotide polymorphism rs1695 of GSTP1 gene with METH-induced symptoms and dependence in a Malaysian population, including Malay, Chinese, Kadazan-Dusun, and Bajau ethnic groups. Genotyping for GSTP1 rs1695 polymorphism from 230 METH-dependent male subjects and 232 healthy male controls was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RLFP). For statistical analyses, the χ2 test and Fisher’s were performed in this research. The results showed a significant difference between GSTP1 rs1695 polymorphism and METH dependence in the Malay and Chinese populations. Our findings suggest that the GSTP1 rs1695 polymorphism may have possibility to methamphetamine dependence in the Malay and Chinese populations but not in other ethnicities. Furthermore, the Malay ethnic group who carried the -105G allele might have a protective role for METH-induced mania.